Studi Proyeksi Kebutuhan Fasilitas Sisi Darat Dan Pengembangan Kota Bandar Udara Ahmad Yani Di Kota Semarang - Wikrana Putra, Pindyandito Surya (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
Ahmad Yani Airport that located in Semarang City is the gateway and transit point for the cities around Semarang. These things made number of passengers and goods are increasing in the Ahmad Yani Airport. The existence Obstacle of Limitation Surfaces on Ahmad Yani Airport did not obstruct the city and the building development therefore it can be built around the airport. The passenger and goods growth rate development Ahmad Yani Airport are not matched by the infrastructure and non-flight facilities growth. In the result of it, there are deficiencies of landside facilities and airport support facilities as a central air transportation. OLS existence is still regarded as a obstruct city growth. This study uses quantitative methods by projection analysis of passengers and flight flow data in previous years. The results are used to find the range of the airport number of passengers and airport facilities volume requirements in the future. The results showed that the rush hour number of passengers at Ahmad Yani Airport is 2864 people and the sum total of passengers per year 57,727,482 in 2035. Terminal area needs a minimum of 12,626 m2 and 38,556 m2 of parking area. The Ahmad Yani Airport required the most supporting room facilities, such as; concession airport room, parking area, pedestrian path, airport hotel, and followed by other facilities. Superimpose and normative analysis showed that the potential placement for the new airport facilities is on the north Ahmad Yani Airport runway.